Development of a novel drug targeting delivery system for cervical cancer therapy. (19th December 2018) - Xiao, Li; Ma, Ni; He, Huimin; Li, Jinmei; Cheng, Sinan; Yang, Qian; Hou, Yifan; Song, Fengying; Jin, Huijuan; Su, Xiaorong; Dong, Jing; Zuo, Ruiye; et al.
Abstract: 'Targeting peptides' have demonstrated their value in diagnostic imaging and therapy and novel peptide probes specific to cervical cancer were developed. In the M13KE phage dodecapeptide (12-mer) peptide library, the phage clone S7 showed the best binding to the cancer cells as confirmed by immunofluorescence and flow cytometry assays, and was selected for continued studies. Its binding peptide, CSP3, was synthesized from the sequence of S7's 12-mer at the N-terminus of the minor coat protein pIII of this M13KE phage vector. The peptide's binding was analyzed by the same assays used for S7. It was also assessed using competitive inhibition and binding to a tissue chip. The results demonstrated that the CSP3 peptide bound to cervical carcinoma cells with high sensitivity and specificity. The positive results indicated that the peptide CSP3, conjugated with nanomaterials and chemotherapeutics, may be developed as a targeting vehicle for therapeutic drug delivery against cervical cancer, especially cervical cancer with multiple drug resistance. For this aim, we prepared a CSP3 conjugated liposome drug delivery system containing doxorubicin (DOX) and microRNA101 (miR101) expression plasmids (CSP3-Lipo-DOX-miR101), and the primary result showed that the system demonstrated significantly enhanced cytotoxicity to SiHa cells and DOX resistant SiHa cells, SiHa/ADR. Our results showed that CSP3 is a cervical cancer targeting 12aa peptide with high specificity and sensitivity, and the CSP3 conjugated drug delivery system, CSP3-Lipo-DOX-miR101 has promising potential for development as an efficient drug system for the therapy of cervical cancer.